The role of UK national ligament registry as additional source of evidence for anterior cruciate ligament reconstruction: Review of the literature and future Perspectives - Boutefnouchet, Tarek; Laios, Thomas; Mathur, Keshav (Journal of Sports Medicine and Therapy, 2017)
Background: There is paucity in studies reporting long-term results following anterior cruciate ligament (ACL) rupture. A UK national ligament registry (NLR) designed to collect demographic, clinical and outcome data on patients undergoing ACL reconstruction was launched in 2013. There was therefore an emergent question on the role of such registry as an additional source of evidence. Study aims: A framework analysis aimed to provide a basis for the evaluation of outcomes following ACL management and formulate a structure of the evidence, which can be derived from the registry. Methods: A systematic approach was adopted to select relevant studies. Qualitative thematic and meta-narrative analyses were conducted. Level-1 registry data were recorded for all primary ACL reconstruction procedures from January to June 2016. Registry data content and validity were evaluated. Results: Seven studies were suitable for analyses yet none defined the pattern of meniscal injury following initial treatment. When reported the incidence varied markedly between 23% and 80%. There was evidence of collection of at least one principal outcome measure in at least 85% of participants across all studies. Thematic analysis identified four key domains of outcome measures (1) intervention selection, (2) Knee stability evaluation, (3) Patient reported outcomes, (4) Radiographic evaluation and risk of secondary osteoarthritis. Graft choice, rate of meniscal and chondral injuries and cumulative risk of revision surgery had incomplete and inconsistent reports. Comparison of demographic and clinical data with the first registry report demonstrated: predominately younger patient population; older female patients at time of intervention; and higher incidence of meniscal tears. Conclusions: Registry data driven quality and research improvement open a new paradigm in ACL reconstruction evidence base and future practice. Early observations have consolidated the importance of associated meniscal injuries in the management of ACL rupture. Further work is needed to improve registry data completeness, accuracy and validity. A proposed data migration process using available technologies can help harmonise data collection without the added burden on clinical services.